Bibliometric study on organizational resilience: trends and future research agenda - David Mhlanga; Mufaro Dzingirai (International Journal of Corporate Social Responsibility (JCSR), 2024)
In an increasingly volatile, uncertain, complex, and ambiguous (VUCA) world, the importance of organizational resilience has grown, yet the scholarly literature on this topic remains fragmented. To address this gap, our study conducted a bibliometric analysis of 469 articles from the Scopus database using VOSViewer software to systematically review and map trends, gaps, and significant contributions in the field. Our analysis revealed key themes such as resilience, crisis management, innovation, COVID-19, dynamic capabilities, sustainability, and change management, which are crucial to understanding organizational resilience. The findings highlight that the United Kingdom and the University of Oulu are significant contributors to this research area, with notable authors including Duchek E., Martinelli E., Santoro G., Williams T.A., and Youssef C.M. playing a pivotal role in advancing this field. By providing a comprehensive overview of institutional affiliations, countries, authors, journals, publications, and keyword co-occurrences, our study not only maps the landscape of organizational resilience research but also identifies critical areas for future inquiry. This contribution enhances both theoretical and practical understandings of organizational resilience, aiding practitioners in developing robust strategies to navigate the challenges of the VUCA world.
Keywords: 650; Crisis Management; Dynamic capabilities; Leadership; Organizational resilience; Performance decline